Chemical composition and in vitro fermentation characteristics of high sugar forage sorghum as an alternative to forage maize for silage making in Tarim Basin, China - Su-jiang ZHANG; Abdul Shakoor Chaudhry; Diky Ramdani; Amerjan Osman; Xue-feng GUO; Grant Raymond Edwards; Long Cheng (Journal of Integrative Agriculture, 2016)
The chemical composition, mineral profile and in vitro fermentation characteristics of maize (MZ), high sugar forage sorghum (HS) and forage sorghum (FS), and silages made from each forage type were measured. The MZ and MZ silage (MZS) had higher crude protein, starch and ether extract contents than both sorghum forages and sorghum silages. HS had higher ash and water-soluble carbohydrate concentrations than FS and MZ. MZ, MZS, HS and HS silage (HSS) had lower neutral detergent fibre, acid detergent fibre and acid detergent lignin than FS and FS silage (FSS). FSS had higher dry matter (DM) and pH than MZS and HSS. HSS contained higher concentrations of P and K than FSS and MZS. MZS and HSS had higher in vitro dry matter and organic matter digestibility, CH4 production, total volatile fatty acids, acetate and propionate than FSS. pH was higher for FSS than for HSS, and ammonia was lower for HSS than for MZS and FSS. HSS had higher gas production than MZS and FSS after 2, 4, 6 and 8 h incubation. MZS had higher gas production than HSS and FSS after 26 and 28 h of incubation. The results indicate that HS may substitute for MZ to make good quality silage. However, animal studies are needed to assess the acceptability and feeding values of HSS vs. MZS for ruminant production.